MENGUNGKAP DETERMINAN KEPUTUSAN PEMBELIAN KONSUMEN DALAM INDUSTRI KULINER: BUKTI DARI ELNA CAKE & BAKERY BUKITTINGGI - Putri, Gustina Bella Eka; Harahap, Heri Faisal; Alfikri (Green Engineering Society, 2024)
This research was conducted in Bukittinggi City. This study aims to analyze product quality, price location and service simultaneously and partially on purchasing decisions. The number of respondents in the study were 100 respondents. Data collection is done through observation, interviews, questionnaires and documentation. The data is processed quantitatively with the data analysis used in the study is the Classical Assumption test (normality test, multicollinearity and heteroscedasticity test), multiple linear regression analysis and statistical tests (multiple correlation analysis, coefficient of determination, F test and t test). The results of the study based on gender are mostly female with a percentage of 79%. Based on age, the majority of respondents are aged 26-35 (39%). Based on the latest education, the majority have a bachelor's degree (61%). Based on the occupation of the majority of workers who are not written on the questionnaire statement or with other choices with a percentage of 32%. The results of statistical tests based on multiple correlation analysis (R) simultaneously the relationship between the independent variable and the dependent variable is stated to be strong at 80,2%, the coefficient of determination (R2) shows the influence of the variables used by 64,3% while the remaining 35,7% is influenced by other factors not explained in this study.